2010
DOI: 10.1093/jxb/erq274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of poplar genotypes on mycorrhizal infection and secreted enzyme activities in mycorrhizal and non-mycorrhizal roots

Abstract: The impact of ectomycorrhiza formation on the secretion of exoenzymes by the host plant and the symbiont is unknown. Thirty-eight F1 individuals from an interspecific Populus deltoides (Bartr.)×Populus trichocarpa (Torr. & A. Gray) controlled cross were inoculated with the ectomycorrhizal fungus Laccaria bicolor. The colonization of poplar roots by L. bicolor dramatically modified their ability to secrete enzymes involved in organic matter breakdown or organic phosphorus mobilization, such as N-acetylglucosami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 64 publications
(84 reference statements)
7
36
0
Order By: Relevance
“…Our results also suggested that the mycorrhizal Pi uptake pathway in poplar is controlled to a large part by the host plant through the differential activation of symbiosis-specific Pi transporter genes. This mechanism is in agreement with the observation that the pattern of secretory enzyme activities of EMs is largely determined by the poplar genotype (Courty et al, 2011).…”
Section: Transcriptional Control Of Poplar Pht1 Gene Expressionsupporting
confidence: 92%
“…Our results also suggested that the mycorrhizal Pi uptake pathway in poplar is controlled to a large part by the host plant through the differential activation of symbiosis-specific Pi transporter genes. This mechanism is in agreement with the observation that the pattern of secretory enzyme activities of EMs is largely determined by the poplar genotype (Courty et al, 2011).…”
Section: Transcriptional Control Of Poplar Pht1 Gene Expressionsupporting
confidence: 92%
“…Unknown factors, which remained to be discovered, are necessary for ascocarp initiation. Courty et al (2010) demonstrated that poplar clones differentially control gene expression of their fungal associates. Tuber fructification could also be under the genetic control of the host.…”
Section: Why Does It Take Several Years For Ascocarp Production To Bementioning
confidence: 99%
“…We believe that facilitation is occurring because the different ECMf species may contribute differently to mobilize different resources by secreting substrate-specific enzymes, not detectable in the microplate assay used here. Moreover, at a species level, functional diversity is also determined by the fungal and the host genetic diversity (Courty et al 2011).…”
Section: Redundancy and Response Diversity Of Functional Groupsmentioning
confidence: 99%
“…The structure and the diversity of ECM communities has been extensively studied across a wide range of forest types (e.g., Courty et al 2008;Tedersoo et al 2010) as well as its response to seasons, tree phenology, host genotype, soil chemistry, or environmental disturbances (e.g., Parrent et al 2006;Courty et al 2007Courty et al , 2010bCourty et al , 2011Dickie et al 2009;Rineau and Garbaye 2009a), but the structure-function relation in these communities has been uncompletely addressed (Leake et al 2002). Studies of ecological preferences and resilience of ECMf species according to disturbances are rare (Elmqvist et al 2003;Folke et al 2004).…”
Section: Introductionmentioning
confidence: 99%